KONDISI SOSIAL EKONOMI PEKERJA PADA PABRIK PT. KEMILAU PERMATA SAWIT DI KENAGARIAN TALANG KUBU TAPAN, KECAMATAN RANAH AMPEK HULU, KABUPATEN PESISIR SELATAN - reza okta yandra; surtani surtani (JURUSAN GEOGRAFI FIS UNP, 2019)
this study aims to determine the conditions of household consumption, living conditions, health conditions, educational conditions and income conditions. This type of research is quantitative descriptive. The population and sample in this study were 51 workers. Sampling uses the proportional random sampling technique. Data collection techniques through questionnaires, observation, and documentation. The data analysis technique using descriptive statistical analysis is the percentage formula put forward by the data. The results of this study indicate that the socio-economic conditions of workers at the PT. Kemilau Permata Palm Factory in Nagari are already good, because they are able to provide all food and non-food needs. minimum area is 47.1%, health conditions are good, if you suffer from minor illness, 80.40% go to a health center, and if severe illness is treated as much as 94.12% at the hospital, the condition of education mostly already covers high school level, and income workers ranged from Rp.2,600,000-Rp.3,500,000 which was 43.14% of all respondents.